Local area networks : - Martin, James (Prentice-Hall, 1989)
This new edition of Martin's best-selling book on LANs - is updated to reflect new technologies. Considers fundamental concepts; the IEEE/ISO Logical Link Control standard; the different methods for medium access control; the construction of enterprise internetwork; and four widely used approaches to network software - IBM and Microsoft, Novel NetWare, TCP/IP, and AppleTalk. For LAN developers, administrators, and technicians.